IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK KELAS 8 DI SMPN 2 KALISAT - Silvia Eka Pratiwi; Maftujianah Maftujianah (ScienceEdu, 2023)
The low motivation of students in learning is a problem that needs to be addressed. Low learning motivation will cause students’ lack enthusiasm in learning which can directly impact student learning outcomes. Based on observations made in class VIII A of SMP Negeri 2 Kalisat, it was found that the students' motivation and enthusiasm for learning were low. Therefore, improvements are needed in learning that can overcome these problems. One of the innovative strategies that can be used as a solution to the problem of low student learning motivation is to use differentiated learning. The purpose of this study was to find out whether differentiated learning can increase students' learning motivation as well as a form of school preparation in implementing the Kurikulum Merdeka at SMP Negeri 2 Kalisat. This study used the Collaborative Classroom Action Research (PTK-K) method which consisted of activity 1, namely pre-cycle and 2 learning cycles. This study uses a qualitative descriptive analysis technique which is carried out on PTK-K data by sorting, simplifying, and grouping, focusing, organizing, and making conclusions on the data obtained. Based on research results, differentiated learning can increase students' learning motivation.This can be seen from the increase in students' learning activities, the enthusiasm of students in learning, and the satisfaction of students in learning according to the results of the interviews. Furthermore, the analysis of the results of the learning motivation questionnaire also showed an increase in learning motivation category from pre-cycle, cycle 1 to cycle 2.